HUBUNGAN PENGETAHUAN, GAYA HIDUP (LIFE STYLE), TINGKAT KECEMASAN DAN STATUS EKONOMI (KEPALA KELUARGA)TERHADAP PERILAKU REMAJA PUTRI DALAM MENGHADAPI PREMENSTRUAL SYNDROME DI MAN 2 SIGLI KECAMATAN MEUREUDU KABUPATEN PIDIE JAYA TAHUN 2018 - aris winandar (Universitas Prima Indonesia, 2018)
Premenstrual syndrome is a condition that consists of multiple physical symptoms, emotions and behaviors experienced by a women before the arrival of the menstrual cycle, which causes disturbances in the function and daily activities. Based on the study preliminary carried out on 10 students of class X and XI in MAN 2 Sigli, there are eight people (80%) are experiencing Pre Menstrual Syndrome and from 8 female students who mangalami Pre Menstrual Syndrome turns out there are 6 people who have less knowledge either teradap Pre menstrual Syndrome and reproductive health. The purpose of this study to determine the relationship of knowledge, lifestyle (life style), anxiety level and economic status of the behavior of the young women in the face of premenstrual syndrome in MAN 2 Sigli subdistrict of Pidie Jaya district Meureudu 2018.This research is descriptive analytic with cross sectional design. The population in this study were all students of class X and XI, 113 people with a sample of 53 students with research time 10 s /d February 12, 2018.The results showed that there was a significant relationship between knowledge with the young women in the face of premenstrual syndrome with P-value of 0.011, lifestyle (life style) teenage daughter in the face of premenstrual syndrome with P-value of 0.006, the anxiety level of the young women in the face of premenstrual syndrome with P-value of 0.001, and there was a significant correlation between economic status (head of family) with the young women in the face of premenstrual syndrome with P-value of 0.023.Suggested to the principal need for increased health education both with counseling, and provide opportunities for teacher training related to adolescent reproductive health so that learners when asking for things related to reproductive health can obtain appropriate information and can be effective in deterrence.